VALIDASI METODA PENENTUAN ANTIOKSIDAN TOTAL (DIHITUNG SEBAGAI ASAM SITRAT) DALAM SAMPEL JERUK SECARA SPEKTOFOTOMETRI DENGAN MENGGUNAKAN OKSIDATOR FeCl3 DAN PENGOMPLEKS ORTO-FENANTROLIN - -, Yefrida; Ulfaningsih, Mega; Loekman, Umiati (Universitas Andalas, 2014)
ABSTRACTAntioxidant is a compound that can be used to obstruct species oxygen reactive, speciesnitrogen, and other free radicals so it can be used degenerative illnesses inhibition. Citric acid isa natural antioxidant that can be found in some kind of oranges. There are some methode thatusually used to determination the antioxidant, such as CUPRAC, DPPH, and FRAP. Objectiveof this research is studied about alternative method to determine total antioxidant that is countedas citric acid by using FeCl3 as an oxidator and o-phenantroline as a complexant reagent. Instudied of appropriateness of this method, validation has been done with parameter linearity,LoD, LoQ, SDR, and recovery with samples orange, kaffir lime, and lime. Base on the research,the regression equation is Y = 0,066 + 117.35 X and R2 = 0.990 with value of LoD is1.15x10-3M and LoQ is 3.86x10-3 M. The value of SDR and recovery in samples orange, kaffir lime, andlime are 1.64%, 0.53% 2.14%, and 100.47%, 93.58%, 93.78%, respectively. Base on validationmethod data, can be concluded that this method appropriate to be used to determination of totalantioxidant for samples orange, kaffir lime, and lime.Keywords : Antioxidant, Validation Method, Spectrophotometry